El Salvador’s FMLN and the Constraints on Leftist Government - Young, Kevin A. (2020)
The 1992 Salvadoran peace accords brought only a superficial version of democracy that remained largely unresponsive to the population. In 2009 the left-wing opposition party, the FMLN, won the presidential elections. However, despite winning some notable progressive reforms, it did not seek, much less achieve, a radical break with the neoliberal policies of prior administrations. Drawing from personal interviews, journalistic reports, polls, academic studies, and official and nongovernmental reports, I argue that the FMLN’s shift away from revolutionary socialism is attributable to several factors: a political and media terrain that still heavily favors the right, the continued influence of the United States government, and private investors’ control over the economy. These forces can also help explain the limitations on progressive governments in other countries.